Potential allelopathic effect of Passiflora foetida on Brassica chinensis and Zea mays - Nornasuha, Yusoff; Nur Hidayah, Napih; Nur Nabilah, Musa; Norhafiza, Yaakob; Mohammad Moneruzzaman, Khandaker (2019)
Interest in developing effective biological weed management system increased because of the awareness of problems associated with the intensive use of herbicides. Thus, allelopathy has been suggested to be one of the possible alternatives for achieving sustainable weed management. Passiflora foetida is a terrestrial perennial herbaceous vine weed and its common name in Malaysia is 'leletup'. Passiflora foetida is the serious weed for several crops and has medicinal value. Previous study had found that P. foetida exhibited high allelopathic activity among 15 weed species that had been tested using sandwich and dish pack method. However, there is limited information about the allelopathic activity of P. betide under soil condition. Thus, this study was carried out to investigate the regulatory role of dry leaf litter and leaf litter aqueous extract of P. foetida on two crop species, which were Brassica chinensis and Zea mays under soil condition. The dry leaf litters were mixed with soil in three concentrations (i.e; 2.5%, 5% and 10%) and leaf litter aqueous extract were prepared and dilutions into 2.5%, 5% and 10% along with control (have no leaf litter) in three replicates. The hypocotyl length, radicle length, chlorophyll content, leaf area, biomass of shoot and biomass of root were recorded after three weeks of experiment. Soil samples were taken from pot culture bioassay and were analyzed for pH, salinity, nitrogen (N), phosphorus (P) and potassium (K). Results showed that the effect of leaf litter was more severe on these plant parameters of both tested species compared to leaf litter extract. There was complete 100% growth inhibition of 8. chinensis when applied with 10% of P. foetida leaf litter. The highest concentration of leaf litter reduced the highest hypocotyl and radicle length. and the lowest concentration reduced the smallest. The total chlorophyll content of both species reduced significantly when applied with leaf litter. However, the salinity increased as the concentration of both treatments increased. Besides, N, P and K were also higher in both treatments compared to control. These results suggested that P. foetida have allelopathic activity and further studies need to be carried out to identify the allelochemicals involved in these inhibitory activities.